2017
DOI: 10.1371/journal.pone.0173529
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro and in vivo evaluation of 3β-[18F]fluorocholic acid for the detection of drug-induced cholestasis in mice

Abstract: IntroductionDrug-induced cholestasis is a liver disorder that might be caused by interference of drugs with the hepatobiliary bile acid transporters. It is important to identify this interference early on in drug development. In this work, Positron Emission Tomography (PET)-imaging with a 18F labeled bile acid analogue was introduced to detect disturbed hepatobiliary transport of bile acids.Methods3β-[18F]fluorocholic acid ([18F]FCA) was prepared by nucleophilic substitution of a mesylated precursor with [18F]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Recently, an 18 F-labeled derivative of unconjugated cholic acid (3-[ 18 F]fluorocholic acid, Fig. 2) was shown to be a substrate of Na + -taurocholate co-transporting polypeptide (NTCP, SLC10A1), OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) (De Lombaerde et al, 2017), all of which are known to be involved in hepatocellular bile acid and bile salt uptake (Stieger, 2011). Furthermore, this bile acid derivative inhibited bile salt export pump (BSEP, ABCB11)-mediated taurocholate and MRP2-mediated estradiol-17ß-glucuronide transport.…”
Section: Liver Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an 18 F-labeled derivative of unconjugated cholic acid (3-[ 18 F]fluorocholic acid, Fig. 2) was shown to be a substrate of Na + -taurocholate co-transporting polypeptide (NTCP, SLC10A1), OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) (De Lombaerde et al, 2017), all of which are known to be involved in hepatocellular bile acid and bile salt uptake (Stieger, 2011). Furthermore, this bile acid derivative inhibited bile salt export pump (BSEP, ABCB11)-mediated taurocholate and MRP2-mediated estradiol-17ß-glucuronide transport.…”
Section: Liver Transportersmentioning
confidence: 99%
“…Furthermore, this bile acid derivative inhibited bile salt export pump (BSEP, ABCB11)-mediated taurocholate and MRP2-mediated estradiol-17ß-glucuronide transport. In mice, pretreatment with rifampicin or bosentan (Fattinger et al, , 2001Stieger et al, 2000) was shown to interfere with hepatocellular transport of 3-[ 18 F]fluorocholic acid (De Lombaerde et al, 2017).…”
Section: Liver Transportersmentioning
confidence: 99%
“…3β-[ 18 F]fluorocholic acid ([ 18 F]FCA), was synthesized and shown to be in vitro a substrate of OATP1B1, OATP1B3, NTCP, BSEP, and MRP2 [92]. In vivo studies in mice pre-treated with the NTCP and the BSEP inhibitor bosentan or with rifampicin (prototypical OATP inhibitor) revealed significant changes in the pharmacokinetics of [ 18 F]FCA when these inhibitors were administered [92]. Recently, this radiotracer has also been applied in different mouse models of liver disease [93].…”
Section: Measuring the Activity Of Bile Acid Transporters With Petmentioning
confidence: 99%
“…PET imaging [20][21][22][23][24][25][26], but so far no imaging agent has been reported for imaging of the EHC. In particular,…”
Section: Accepted Manuscriptmentioning
confidence: 99%